Higher education: Sine qua non condition for a latin american integration in Pablo Guadarrama’s proposal - Polo Carrillo, Heyner (2023)
This article will explain how higher education has some of the necessary tools to combat the elements that prevent “Latin American integration”, a goal that the Cuban philosopher Pablo Guadarrama considers of utmost importance. To do this, first its “transcendental work” in society is valued, how it questions the alienating phenomena of globalization; Consequently, its function in the face of the problem of culture will be analyzed; to finally establish its relationship with historical memory, a key issue to understand the reason for an Integration like Latin America.